Camera trap distance sampling for terrestrial mammal population monitoring: lessons learnt from a UK case study. Issue 5 (13th May 2022) - Mason, Samantha S.; Hill, Russell A.; Whittingham, Mark J.; Cokill, Jim; Smith, Graham C.; Stephens, Philip A.
Abstract: Accurate and precise density estimates are crucial for effective species management and conservation. However, efficient monitoring of mammal densities over large spatial and temporal scales is challenging. In the United Kingdom, published density estimates for many mammals, including species considered to be common, are imprecise. Camera trap distance sampling (CTDS) can estimate densities of multiple species at a time and has been used successfully in a small number of studies. However, CTDS has typically been used over relatively homogeneous landscapes, often over large time scales, making monitoring changes (by repeating surveys) difficult. In this study, we deployed camera traps at 109 sites across an area of 2725 km 2 of varied habitat in North‐East England, United Kingdom. The 4‐month survey generated 51 447 photos of wild mammal species. Data were sufficient for us to use CTDS to estimate the densities of eight mammal species across the whole‐survey area and within four specific habitats. Both survey‐wide and habitat‐specific density estimates largely fell within previously published density ranges and our estimates were amongst the most precise produced for these species to date. Lower precision for some species was typically due to animals being missed by the camera at certain distances, highlighting the need for careful consideration of practical and methodological decisions, such as how high to set cameras and where to left‐truncate data. Although CTDS is a promising methodology for determining densities of multiple species from one survey, species‐specific decisions are still required and these cannot always be generalized across species types and locations. Taking the United Kingdom as a case study, our study highlights the potential for CTDS to be used on a national scale, although the scale of the task suggests that it would need to be integrated with a citizen science approach. Abstract : In this study we use camera trap distance sampling to estimate both survey‐wide and habitat‐specific densities for a range of mammal species in north east England. We show that our density estimates are similar to other published estimates but with a higher level of precision. We discuss the opportunities and challenges of using this method for national‐level mammal monitoring, taking the UK as a case study.